Cultivating Cultural Education Values of Islam Nusantara in MA (Islamic Senior High School) Ali Maksum Krapyak - Widodo, Sembodo Ardi (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2016)
This research aims to determine the cultural education values of Islam Nusantara atIslamic Senior High School of Ali Maksum Krapyak Yogyakarta and how those values are taught through education. This researchuses qualitative approach by usingdata collection technique through observation, interviews, and documentation. The process of analysis data used is qualitative. The results of this study show that Islam Nusantara is an Islamic style of Indonesia, a combination of Islamic theological values with the local traditions, culture and customs. There are three pillars in Islam Nusantara, there arethought, movement, and 'amaliyya (action) and there are five signs of Islam Nusantara, namely reform (ishlahiyyah), tawazuniyyah, tathawwu'iyyah, akhlaqiyyah (politeness), and tasamuh;The cultural education values of Islam Nusantara in MA Ali Maksum is the value of nationalism, diversity (pluralism), and the value of NU (tasamuh, tawazun, tawasuth); The madrasah activities consist ofMuludan, grave pilgrimage, halal bi halal, Muharroman, haul of the founder (dies natalis), competitions reading kitab kuning(yellow books), etc., that those are the typical product of Islam Nusantara.